Coagulant material, preparation method and application
By preparing aluminum-iron composite coagulant materials, the existing fluorine-removing coagulant materials have solved the problems of low fluorine removal efficiency, small and light flocs, and poor sedimentation performance, and the effects of rapid and efficient fluorine removal, fast floc growth rate, good sedimentation performance and low aluminum residue are achieved.
Patent Information
- Application Number
- CN202510285728.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
AI Technical Summary
The existing fluorine-removing coagulant materials have problems such as low fluorine removal efficiency, small and light flocs, and poor settlement performance, which are difficult to meet strict emission standards.
Using a preparation method of a ferro-aluminum composite coagulant material, a pre-hydrolyzed silane coupling agent is mixed with a mixed solution of aluminum chloride and ferro chloride, and then a sodium hydroxide solution is added and allowed to stand and mature to form a covalent composite coagulant of aluminum and ferrochloride.
The fluorine removal material has both fast and efficient fluorine removal ability, fast floc growth rate, good sedimentation performance and low aluminum residue. It can effectively remove fluorine within a wide pH range and is stable and suitable.
Smart Images

Figure CN119797545A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a coagulant material, a preparation method and an application thereof. Background Art
[0002] With the rapid development of the semiconductor industry, coking industry, steel smelting and other electronic industries, fluoride-containing wastewater has gradually increased. Excessive discharge of fluoride-containing wastewater has serious negative effects on the environment, human health and ecosystems. Fluoride-containing wastewater discharged into rivers, lakes and other water bodies will lead to an increase in the concentration of fluoride ions in the water body, affecting the survival and reproduction of aquatic organisms and destroying the balance of the aquatic ecosystem. Long-term drinking of water sources with excessive fluoride content will cause fluorosis symptoms such as dental fluorosis and skeletal fluorosis, and even cause diseases of the nervous system and cardiovascular system, posing a threat to human life safety. The World Health Organization (WHO) recommends a fluoride concentration of 1.5 milligrams per liter (mg / L) in drinking water, and China's latest "Standards for Drinking Water Hygiene" (GB5749-2022) stipulates that the limit value of fluoride in drinking water is 1.0 mg / L. In order to meet increasingly stringent fluoride removal standards, fluoride removal technology is also constantly developing.
[0003] The traditional calcium salt precipitation method can only reduce the fluoride content in wastewater to about 15 mg / L, which is difficult to meet strict emission standards. Fluoride removal by coagulation and sedimentation has the advantages of high efficiency, economy, and simple operation, and its application scope is constantly expanding. Fluoride removal coagulant materials have evolved from simple aluminum / iron salt coagulant materials to composite coagulant materials. Currently, the commonly used fluoride removal coagulant materials have problems such as low fluoride removal efficiency, small and light flocs, and poor sedimentation performance.
[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0005] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide a coagulant material, a preparation method and an application thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a coagulant material comprises the following steps: S1, adding a silane coupling agent into water for pre-hydrolysis to obtain a pre-hydrolysis solution; S2, preparing a mixed solution of aluminum chloride and ferric chloride, stirring until completely dissolved and uniformly mixed, wherein the mass ratio of the aluminum chloride to the ferric chloride is 9:1-5:5; S3, mixing the pre-hydrolysis solution with the mixed solution of aluminum chloride and ferric chloride, and stirring evenly, wherein the ratio of the total mass of silicon in the silane coupling agent to the total mass of aluminum and iron is 0.1-0.5; S4, adding sodium hydroxide solution dropwise to the mixed solution to adjust the alkalinity to a mass ratio of [OH] / [Al+Fe] of 1 to 2; S5. Allow the solution after adjusting the alkalinity to stand and mature to obtain an aluminum-iron covalent composite coagulant.
[0007] Furthermore, in step S1, the silane coupling agent is triaminopropyltriethoxysilane with a concentration of 0.01-0.02 mol / L.
[0008] Furthermore, in step S1, the volume ratio of the silane coupling agent to water is 1:20.
[0009] Furthermore, in step S2, the concentration of the aluminum chloride solution is 0.045-0.05 mol / L, and the concentration of the ferric chloride solution is 0.005-0.025 mol / L.
[0010] Furthermore, in step S4, the concentration of the sodium hydroxide solution is 0.5-1 mol / L.
[0011] Furthermore, in step S1, stirring is performed during the pre-hydrolysis process, the stirring speed is 600-700 r / min, and the stirring time is 20-30 minutes.
[0012] Furthermore, in step S3, the stirring speed of the mixed solution and the pre-hydrolysis solution after mixing is 600-700 r / min, and the stirring time is 30-40 minutes.
[0013] Furthermore, in step S5, the standing and aging time is 4 to 6 hours.
[0014] A coagulant material is prepared by the preparation method.
[0015] The application of the coagulant material in fluorine removal.
[0016] The present invention has the following beneficial effects: In view of the problems of low defluorination efficiency, small and light flocs, poor sedimentation performance, etc. in existing defluorination coagulant materials, the present invention provides an aluminum-iron composite coagulant material and a preparation method thereof. The prepared defluorination coagulant material has the characteristics of fast and efficient defluorination ability, fast floc growth rate, good sedimentation performance, and low aluminum residue. The defluorination material can achieve defluorination in a wide pH range and can be stably applied.
[0017] Compared with the prior art, the present invention has the following advantages: (1) Strong fluoride removal ability. Compared with the widely used commercial coagulant polyaluminium chloride, under the same experimental conditions, its fluoride removal ability is better than that of polyaluminium chloride coagulant. When the dosage is 1.85mmol / L, the aluminum-iron composite coagulant has a 46% increase in fluoride ion removal ability compared with polyaluminium chloride, and the fluoride concentration in water is reduced to 1.5mg / L, which meets the fluoride removal requirements for drinking water or industrial water.
[0018] (2) The composite coagulant has a slow hydrolysis rate and a wide pH range, making it suitable for different water quality conditions.
[0019] (3) Strong stability. The composite coagulant is sealed and stored at room temperature. It is not easy to decompose or deteriorate. The storage time is more than 1 times that of polyaluminium chloride solution.
[0020] (4) The flocs grow rapidly and have good settling performance. Flocs can be seen settling within 30 minutes of static sedimentation. The flocs are large and dense. No floc settling process is observed during the polyaluminium chloride defluorination process.
[0021] (5) Low metal residue. The composite coagulant forms Al-O-Si and Fe-O-Si covalent bonds, and the hydrolysis and polymerization processes proceed in an orderly manner, which improves the stability of the coagulant. This helps to form a larger floc structure, thereby improving the removal efficiency of the coagulant and reducing the residual aluminum ions in the water.
[0022] (6) Easy to dissolve and use. The composite coagulant powder dissolves quickly, mixes evenly, and is easy to use.
[0023] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The remaining Changes with the dosage of aluminum-iron composite coagulant. DETAILED DESCRIPTION
[0025] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0026] In some embodiments, a method for preparing a coagulant material comprises the following steps: (1) Add 0.01~0.02 mol / L triaminopropyltriethoxysilane to a certain amount of water for pre-hydrolysis, with a volume ratio of 1:20 and a mass ratio of Si: (Al+Fe) of 0.1~0.5, and stir for 20~30 min; (2) Prepare a mixed solution of 0.045-0.05 mol / L aluminum chloride and 0.005-0.025 mol / L ferric chloride, with an Al / Fe mass ratio of 9:1-5:5, and stir for 30-40 minutes to completely dissolve and mix them evenly; (3) Mix the solutions obtained in step (1) and step (2) evenly and stir for 30 to 40 minutes; (4) adding 0.5-1 mol / L sodium hydroxide to the mixed solution obtained in step (3) to make the alkalinity (i.e., the mass ratio of [OH] / [AlFe]) be: (5) The solution obtained in step (4) is allowed to stand and mature for 4 to 6 hours to obtain an Al-Fe covalent composite coagulant.
[0027] In a preferred embodiment, in step (1), the volume of triaminopropyltriethoxysilane used is 3-4 mL.
[0028] In a preferred embodiment, in step (1), the stirring speed is 600-700 r / min, and the stirring time is 20-30 min.
[0029] In a preferred embodiment, in step (3), the stirring speed is 600-700 r / min, and the stirring time is 30-40 min.
[0030] The specific embodiments of the present invention are further described below.
[0031] Example 1
[0032] Preparation of fluoride removal composite coagulant (1) Add 3.53 mL of triaminotriethoxysilane to 70 mL of water and pre-hydrolyze for 30 min at a stirring speed of 700 r / min; (2) Add 6.00 g of aluminum chloride to 30 mL of water to prepare an aluminum chloride solution, and add 0.81 g of ferric chloride to 10 mL of water to prepare a ferric chloride solution. Mix well and stir for 30 min. (3) The solutions obtained in step (1) and step (2) were mixed evenly and stirred for 40 minutes; (4) Add 4 g of sodium hydroxide to 140 mL of water to prepare a sodium hydroxide solution, and slowly add it dropwise for 2.5 hours using a constant flow pump; (5) The solution obtained in the above step (4) is allowed to stand and mature for 5 hours to obtain an Al-Fe covalent composite coagulant.
[0033] Fluoride removal evaluation test 0.37, 0.74, 1.11, 1.48, 1.85mmol / L Al-Fe covalent composite coagulant was added to 200mL fluoride ion solution with an initial concentration of 10mg / L, and stirred rapidly for 2min at a speed of 1000r / min, then stirred slowly for 10min, and allowed to settle for 30min. 5mL of supernatant was taken and the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was measured to be reduced to 6.1, 3.3, 2.7, 1.8, and 1.5mg / L, respectively.
[0034] Example 2
[0035] Preparation of fluoride removal composite coagulant (1) Add 3.53 mL of triaminotriethoxysilane to 70 mL of water and pre-hydrolyze for 30 min at a stirring speed of 700 r / min; (2) Add 5.33 g of aluminum chloride to 30 mL of water to prepare an aluminum chloride solution, and add 1.62 g of ferric chloride to 10 mL of water to prepare a ferric chloride solution, mix well, and stir for 30 minutes; (3) The solutions obtained in step (1) and step (2) were mixed evenly and stirred for 40 minutes; (4) Add 4 g of sodium hydroxide to 140 mL of water to prepare a sodium hydroxide solution, and slowly add it dropwise for 2.5 hours using a constant flow pump; (5) The solution obtained in the above step (4) is allowed to stand and mature for 5 hours to obtain an Al-Fe covalent composite coagulant.
[0036] Fluoride removal evaluation test 0.37, 0.74, 1.11, 1.48, 1.85mmol / L Al-Fe covalent composite coagulant was added to 200mL fluoride ion solution with an initial concentration of 10mg / L, and stirred rapidly for 2min at a speed of 1000r / min, then stirred slowly for 10min, and allowed to settle for 30min. 5mL of supernatant was taken and the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was measured to be reduced to 6.0, 4.4, 3.2, 2.6, and 1.9mg / L, respectively.
[0037] Example 3
[0038] Preparation of fluoride removal composite coagulant (1) Add 3.53 mL of triaminotriethoxysilane to 70 mL of water and pre-hydrolyze for 30 min at a stirring speed of 700 r / min; (2) Add 4.67 g of aluminum chloride to 30 mL of water to prepare an aluminum chloride solution, and add 2.43 g of ferric chloride to 10 mL of water to prepare a ferric chloride solution, mix well, and stir for 30 minutes; (3) The solutions obtained in step (1) and step (2) were mixed evenly and stirred for 40 minutes; (4) Add 4 g of sodium hydroxide to 140 mL of water to prepare a sodium hydroxide solution, and slowly add it dropwise for 2.5 hours using a constant flow pump; (5) The solution obtained in the above step (4) is allowed to stand and mature for 5 hours to obtain an Al-Fe covalent composite coagulant.
[0039] Fluoride removal evaluation test 0.37, 0.74, 1.11, 1.48, 1.85mmol / L Al-Fe covalent composite coagulant was added to 200mL fluoride ion solution with an initial concentration of 10mg / L, and stirred rapidly for 2min at a speed of 1000r / min, then stirred slowly for 10min, and allowed to settle for 30min. 5mL of supernatant was taken and the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was measured to be reduced to 5.6, 4.7, 3.7, 2.7, and 2.2mg / L, respectively.
[0040] Example 4
[0041] Preparation of fluoride removal composite coagulant (1) Add 3.53 mL of triaminotriethoxysilane to 70 mL of water and pre-hydrolyze for 30 min at a stirring speed of 700 r / min; (2) Add 4.00 g of aluminum chloride to 30 mL of water to prepare an aluminum chloride solution, and add 3.24 g of ferric chloride to 10 mL of water to prepare a ferric chloride solution, mix well, and stir for 30 minutes; (3) The solutions obtained in step (1) and step (2) were mixed evenly and stirred for 40 minutes; (4) Add 4 g of sodium hydroxide to 140 mL of water to prepare a sodium hydroxide solution, and slowly add it dropwise for 2.5 hours using a constant flow pump; (5) The solution obtained in the above step (4) is allowed to stand and mature for 5 hours to obtain an Al-Fe covalent composite coagulant.
[0042] Fluoride removal evaluation test 0.37, 0.74, 1.11, 1.48, and 1.85 mmol / L Al-Fe covalent composite coagulant were added to 200 mL fluoride ion solution with an initial concentration of 10 mg / L, and the mixture was rapidly stirred for 2 min at a speed of 1000 r / min. The mixture was then slowly stirred for 10 min and allowed to settle for 30 min. 5 mL of supernatant was taken and the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was found to be reduced to 5.8, 4.4, 3.5, 2.6, and 1.9 mg / L, respectively.
[0043] Example 5
[0044] Preparation of fluoride removal composite coagulant (1) Add 3.53 mL of triaminotriethoxysilane to 70 mL of water and pre-hydrolyze for 30 min at a stirring speed of 700 r / min; (2) Add 3.33 g of aluminum chloride to 30 mL of water to prepare an aluminum chloride solution, and add 4.05 g of ferric chloride to 10 mL of water to prepare a ferric chloride solution, mix well, and stir for 30 min; (3) The solutions obtained in step (1) and step (2) were mixed evenly and stirred for 40 minutes; (4) Add 4 g of sodium hydroxide to 140 mL of water to prepare a sodium hydroxide solution, and slowly add it dropwise for 2.5 hours using a constant flow pump; (5) The solution obtained in the above step (4) is allowed to stand and mature for 5 hours to obtain an Al-Fe covalent composite coagulant.
[0045] Fluoride removal evaluation test 0.37, 0.74, 1.11, 1.48, 1.85mmol / L Al-Fe covalent composite coagulant was added to 200mL fluoride ion solution with an initial concentration of 10mg / L, and stirred rapidly for 2min at a speed of 1000r / min, then stirred slowly for 10min, and allowed to settle for 30min. 5mL of supernatant was taken and the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was measured to be reduced to 6.5, 4.5, 3.4, 2.6, and 2.3mg / L, respectively.
[0046] As an example, Figure 1 It shows that when the defluorination composite coagulant and polyaluminium chloride coagulant of Examples 1-5 of the present invention are used respectively, the residual The concentration changes with the dosage. Reaction conditions: The initial concentration was 10 mg / L, pH = 6.5-7, the coagulant dosage was 0.37, 0.74, 1.11, 1.48, and 1.85 mmol / L, respectively, the solution volume was 200 mL, the rapid stirring time was 2 min, the slow stirring time was 10 min, and the sedimentation was allowed to stand for 30 min.
[0047] Compared with existing defluorination coagulants (such as polyaluminium chloride coagulants), the defluorination composite coagulant material provided by the present invention has the advantages of rapid and efficient defluorination capability, fast floc growth rate, good sedimentation performance and low aluminium residue.
[0048] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing a coagulant material, characterized in that: The following steps are involved: S1, adding a silane coupling agent into water for pre-hydrolysis to obtain a pre-hydrolysis solution; S2, preparing a mixed solution of aluminum chloride and ferric chloride, stirring until completely dissolved and uniformly mixed, wherein the mass ratio of the aluminum chloride to the ferric chloride is 9:1-5:5; S3, mixing the pre-hydrolysis solution with the mixed solution of aluminum chloride and ferric chloride, and stirring evenly, wherein the ratio of the total mass of silicon in the silane coupling agent to the total mass of aluminum and iron is 0.1-0.5; S4, adding sodium hydroxide solution dropwise to the mixed solution to adjust the alkalinity to a mass ratio of [OH] / [Al+Fe] of 1 to 2; S5. Allow the solution after adjusting the alkalinity to stand and mature to obtain an aluminum-iron covalent composite coagulant.
2. The preparation method according to claim 1, characterized in that In step S1, the silane coupling agent is triaminopropyltriethoxysilane with a concentration of 0.01-0.02 mol / L.
3. The preparation method according to claim 2, characterized in that: In step S1, the volume ratio of the silane coupling agent to water is 1:
20.
4. The preparation method according to claim 3, characterized in that: In step S2, the concentration of the aluminum chloride solution is 0.045-0.05 mol / L, and the concentration of the ferric chloride solution is 0.005-0.025 mol / L.
5. The preparation method according to claim 4, characterized in that: In step S4, the concentration of the sodium hydroxide solution is 0.5-1 mol / L.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S1, stirring is performed during the pre-hydrolysis process, the stirring speed is 600-700 r / min, and the stirring time is 20-30 minutes.
7. The preparation method according to any one of claims 1 to 5, characterized in that: In step S3, the mixed solution and the pre-hydrolysis solution are stirred at a speed of 600-700 r / min and a stirring time of 30-40 minutes.
8. The preparation method according to any one of claims 1 to 5, characterized in that: In step S5, the standing and aging time is 4 to 6 hours.
9. A coagulant material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the coagulant material according to claim 9 in defluorination.
Citation Information
Patent Citations
Preparation method of PSAF (polysilicate aluminum ferric) flocculant
CN105481072A
Cited By
Silane-bonded aluminum-silicon-based supramolecular defluorination coagulant as well as preparation method and application thereof
CN120794143A
Silane-bonded aluminosilicate-based supermolecular defluoridation coagulant, preparation method and application thereof
CN120794143B